Hepatitis B virus X protein promotes hepatocarcinogenesis via the activation of HMGA2/STC2 signaling to counteract oxidative stress-induced cell death. (30th March 2022) - Huang, Fung-Yu; Wong, Danny Ka-Ho; Mak, Lung-Yi; Cheung, Tan-To; Seto, Wai-Kay; Yuen, Man-Fung
Abstract: Chronic hepatitis B virus (HBV) infection can cause oxidative stress and induce cell death. The mechanisms by which cells overcome oxidative stress to survive remain largely unknown. Here, we used human sera, liver tissues and cell lines to study how HBV modulates cellular pathways to counteract oxidative stress-induced cell death. We found high-mobility group AT-hook 2 (HMGA2), an architectural transcription factor is upregulated in hepatocellular carcinoma (HCC) tissues and cell lines. Elevated serum HMGA2 is significantly associated with viral load in HBV carriers, and HBV-related HCC. We showed that HBV X protein (HBx) encoded by HBV-induced cell growth via HMGA2 activation. The growth-promoting effect is abolished when HMGA2 is suppressed. Ectopic HBx expression induced DNA damage and oxidative stress. HMGA2 silencing reduced oxidative stress in HBx-expressing cells. Cytoprotective stanniocalcin 2 (STC2) protein is a downstream target of HMGA2. Consistent with the findings in HMGA2, STC2 mRNA and protein expression are upregulated in HCC tissues. Elevated serum STC2 is also associated with viral load in HBV carriers, and HCC. STC2 is transcriptionally upregulated by HBx and HMGA2 to elicit cytoprotection against apoptosis. STC2 knockdown disrupted Bax/Bcl-2 balance that increased cytochrome c release, caspase 3/7 activity and apoptosis, and thus abolished the growth-promoting effect of HMGA2. Clinical relevance of HBx/HMGA2/STC2 signaling is evidenced by the significant correlation of serum HMGA2/STC2 in active HBV infection and HCC. These findings reveal a novel HBx regulatory HMGA2/STC2 pathway in counteracting reactive oxygen species-induced cell death. HMGA2 and STC2 may be therapeutic targets for prevention of hepatocarcinogenesis in chronic HBV infection. Abstract : HBx protein encoded by HBV induced HMGA2 and STC2 expression. The HBx/HMGA2/STC2 signaling promotes hepatocarcinogenesis by protecting cells from ROS-induced apoptosis. Graphical Abstract: